(untitled) (Semiárida, 2020)
The objective of this experience was to determine the effects of nitrogen fertilizars on the grain yield and grain protein content. Generally both features are negatively associated.The cultivars Buck Pucará and Buck Cencerro were analyzed. Grain yield (kg/ha), protein content (%) and protein yield (kg/ha) were determinated. The correlations between these variable were analyzed. The early application of nitrogen fertilizer did not bring in significants increments of grain bruts protein although there are high response in the late applications. No grain yield increments were observed if fertilizers application are delayed. The efficiency of the proved genotypes was determinated by the assimilated nitrogen evolution.